Does self-sampling for human papilloma virus testing have the potential to increase cervical cancer screening? An updated meta-analysis of observational studies and randomized clinical trials - Di Gennaro, Gianfranco; Licata, Francesca; Trovato, Alessandro; Bianco, Aida (Frontiers in Public Health, 2022)
Objectives A meta-analysis was conducted to examine the effectiveness of HPV self-sampling proposal on cervical cancer screening (CCS) uptake when compared with an invitation to have a clinician to collect the sample. Secondary outcomes were acceptability and preference of self-sampling compared to clinician-collected samples. Methods The present systematic review and meta-analysis followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Studies examining the CCS uptake comparing self-sampling over invitation to be sampled by an healthcare professional and examining the proportion of women accepting or preferring self-sampling vs. clinician-collected sampling were included. The CCS uptake was also explored according to strategy of self-samplers' distribution, collection device type and screening status. Peters' test and Funnel Plot inspection were used to assess the publication bias. Quality of the studies was assessed through Cochrane Risk of Bias and NIH Quality Assessment tools. Results One hundred fifty-four studies were globally identified, and 482,271 women were involved. Self-sampling procedures nearly doubled the probability (RR: 1.8; 95% CI: 1.7–2.0) of CCS uptake when compared with clinician-collected samples. The opt-out (RR: 2.1; 95% CI: 1.9–2.4) and the door-to-door (RR: 1.8; 95% CI: 1.6–2.0) did not statistically significant differ (p = 1.177) in improving the CCS uptake. A higher relative uptake was shown for brushes (RR: 1.6; 95% CI: 1.5–1.7) and swabs (RR: 2.5; 95% CI: 1.9–3.1) over clinician-collected samples. A high between-studies variability in characteristics of sampled women was shown. In all meta-analyses the level of heterogeneity was consistently high (I2 > 95%). Publication bias was unlikely. Conclusions Self-sampling has the potential to increase participation of under-screened women in the CCS, in addition to the standard invitation to have a clinician to collect the sample. For small communities door-to-door distribution could be preferred to distribute the self-sampler while; for large communities opt-out strategies should be preferred over opt-in. Since no significant difference in acceptability and preference of device type was demonstrated among women, and swabs and brushes exhibited a potential stronger effect in improving CCS, these devices could be adopted.